Language skills development in children with congenital Zika virus syndrome - da Silva, Nathani Cristina [UNESP]; Pinato, Luciana [UNESP]; Ribeiro, Erlane M.; Giacheti, Celia Maria [UNESP] (Elsevier, 2023)
Background: The characterization of the phenotype of children with congenital Zika virus syndrome (CZS) is an ongoing process, since many characteristics can only be described with the advancing age of children providing some insights into the long-term sequelae. Aims: To describe emerging findings on the impact of CZS on language development in children with CZS in a 4-year longitudinal study. Methods and procedures: 39 boys and 44 girls with CZS were allocated into four groups according to age ranging from 12 to 36 months. Language development was assessed using the Early Language Milestone Scale. Outcomes and results: Visual, expressive, and receptive auditory skills of patients were lower than expected for their age. Despite producing vowel sounds, they did not babble; despite present hearing, the majority of the children did not understand simple commands. In over 4 years of follow-up, there was no evolution in language parameters, with the children stagnating at the language skills corresponding to 3 months of age. Conclusions and implications: Most children with CZS are not able to produce vocalic sounds, but some may be able to communicate basic needs through alternative communication. What this paper adds?: Some babies with CZS died prenatally, at birth, or in the first year of life due to associated complications such as respiratory infection, dysphagia, and epilepsy. However, the functionality of the future remains uncertain for surviving babies. This study adds information about the impact of Zika Virus on the central nervous system and, consequently, the severity and complexity of the CZS language. Over 4 years of follow-up, no evolution in language parameters was observed in children with CSZ. Children with CZS demonstrate severe neurodevelopmental impairment, stagnating in language skills at the age of 3 months. In the future, some of them may be able to communicate their basic needs through alternative communication.
Keywords: Brain; Congenital Zika virus syndrome; Language development; Neurodevelopment